THE USE OF MATRICES IN SERVICE MARKETING RESEARCH (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
The purpose of this study is to analyze the applicability of various marketing methods and tools for building a marketing strategy for service companies. We have discussed four marketing matrices and explore their productiveness in service marketing researches. As a result, we find out that matrices are the most productive methods for service companies and they have many advantages. They provide an opportunity։ to develop a strategic complex of measures aimed at increasing business turnover; to use several strategies at the same time; to find a situation in the market in which the company will be protected and will be able to independently influence the competitive forces in their market; to predict the threat level of competitors for business activity; to the company owners to assess their company's capabilities against their main competitors; to facilitate the identification of competitive advantages and market opportunities so that companies can develop or create products, services and market strategies.
Keywords: the use of matrices; BCG matrix; Ansoff matrix; Porter’s Five Forces matrix; Competitive Profile matrix